Cerebrospinal fluid biomarker candidates of schizophrenia: where do we stand? - Vasic, Nenad; Wolf, Robert Christian (European archives of psychiatry and clinical neuroscience, 2012)
Here, we review the cerebrospinal fluid (CSF) candidate markers with regard to their clinical relevance as potential surrogates for disease activity, prognosis assessment, and predictors of treatment response. We searched different online databases such as MEDLINE and EMBASE for studies on schizophrenia and CSF. Initial studies on cerebrospinal fluid in patients with schizophrenia revealed increased brain-blood barrier permeability with elevated total protein content, increased CSF-to-serum ratio for albumin, and intrathecal production of immunoglobulins in subgroups of patients. Analyses of metabolites in CSF suggest alterations within glutamatergic neurotransmission as well as monoamine and cannabinoid metabolism. Decreased levels of brain-derived neurotrophic factor and nerve growth factor in CSF of first-episode patients with schizophrenia reported in recent studies point to a dysregulation of neuroprotective and neurodevelopmental processes. Still, these findings must be considered as non-specific. A more profound characterization of the particular psychopathological profiles, the investigation of patients in the prodromal phase or within the first episode of schizophrenia promoting longitudinal investigations, implementation of different approaches of proteomics, and rigorous adherence to standard procedures based on international CSF guidelines are necessary to improve the quality of CSF studies in schizophrenia, paving the way for identification of syndrome-specific biomarker candidates.